Ferroelectricity emerging in strained (111)-textured ZrO2 thin films - Fan, Zhen (2016)
(Anti-)ferroelectricity in complementary metal-oxide-semiconductor (CMOS)-compatible binary oxides have attracted considerable research interest recently. Here, we show that by using substrate-induced strain, the orthorhombic phase and the desired ferroelectricity could be achieved in ZrO2thin films. Our theoretical analyses suggest that the strain imposed on the ZrO2 (111) film by the TiN/MgO (001) substrate would energetically favor the tetragonal (t) and orthorhombic (o) phases over the monoclinic (m) phase of ZrO2, and the compressive strain along certain ⟨11-2⟩ directions may further stabilize the o-phase. Experimentally ZrO2thin films are sputtered onto the MgO (001) substrates buffered by epitaxial TiN layers. ZrO2thin films exhibit t- and o-phases, which are highly (111)-textured and strained, as evidenced by X-ray diffraction and transmission electron microscopy. Both polarization-electric field (P-E) loops and corresponding current responses to voltage stimulations measured with appropriate applied fields reveal the ferroelectric sub-loop behavior of the ZrO2films at certain thicknesses, confirming that the ferroelectric o-phase has been developed in the strained (111)-textured ZrO2films. However, further increasing the applied field leads to the disappearance of ferroelectric hysteresis, the possible reasons of which are discussed.